Molecular Characterization and Immuno-Reactivity Patterns of a Novel Plasmodium falciparum Armadillo-Type Repeat Protein, PfATRP - Amlabu, Emmanuel; Ilani, Philip; Opoku, Grace; Nyarko, Prince B.; Quansah, Evelyn; Thiam, Laty G.; Anim, Manfred; Ayivor-Djanie, Reuben; Akuh, Ojo-ajogu; Mensah-Brown, Henrietta; Rayner, Julian C.; Awandare, Gordon A. (Frontiers in Cellular and Infection Microbiology, 2020)
Nearly half of the genes in the Plasmodium falciparum genome have not yet been functionally investigated. We used homology-based structural modelling to identify multiple copies of Armadillo repeats within one uncharacterized gene expressed during the intraerythrocytic stages, PF3D7_0410600, subsequently referred to as P. falciparum Armadillo-Type Repeat Protein (PfATRP). Soluble recombinant PfATRP was expressed in a bacterial expression system, purified to apparent homogeneity and the identity of the recombinant PfATRP was confirmed by mass spectrometry. Affinity-purified α-PfATRP rabbit antibodies specifically recognized the recombinant protein. Immunofluorescence assays revealed that α-PfATRP rabbit antibodies reacted with P. falciparum schizonts. Anti-PfATRP antibody exhibited peripheral staining patterns around the merozoites. Given the localization of PfATRP in merozoites, we tested for an egress phenotype during schizont arrest assays and demonstrated that native PfATRP is inaccessible on the surface of merozoites in intact schizonts. Dual immunofluorescence assays with markers for the inner membrane complex (IMC) and microtubules suggest partial colocalization in both asexual and sexual stage parasites. Using the soluble recombinant PfATRP in a screen of plasma samples revealed that malaria-infected children have naturally acquired PfATRP-specific antibodies.